Deskripsi Kemampuan Literasi Matematika Siswa SMP Negeri 1 Batanghari Dalam Pemecahan Masalah - Azahra, Siti Rahma; Nurhanurawati, Nurhanurawati; Caswita, Caswita (Universitas PGRI Madiun, 2022)
Mathematical literacy ability is defined as a person's ability to formulate, apply and interpret mathematics in various contexts, including the ability to reason mathematically and use concepts, procedures, and facts to describe, explain or predict phenomena/events. The purpose of this study was to describe the profile of the mathematical literacy ability of seventh grade students of SMP N 1 Batanghari, East Lampung on the material of triangles and quadrilaterals. This research is a quantitative research with descriptive method. The subjects in this study were 28 students of class VII. Based on the data and analysis of the results of the study, it was found that the percentage of questions at level 1 students were able to solve problems using routine procedures and direct questions in the fairly good category. While the questions at level 2 and level 3 are still not good. The results of interviews with several students related to problem solving who made mistakes due to the difficulty of understanding the problem from the information provided without understanding the meaning and information of what was known.